PREVALENCE OF CERVICOGENIC HEADACHE AMONG YOUNG POPULATION - Kanniappan, Vadivelan; Abraham, Shalu Sam; Veeragoudhaman, T. S. (International Journal of Research -GRANTHAALAYAH, 2022)
Background: Cervicogenic headache (CEH) is a secondary headache characterized by unilateral headache, signs of neck involvement and often worsened by neck movement, sustained awkward head position. Excessive stress to the neck, degenerative conditions like osteoarthritis, a prolapsed disc in the neck, or a whiplash injury can cause cervicogenic headache. The current young generation uses smart phones for a high amount of time. The researchers found that there is a strong positive correlation with pain intensity, headache and neck disability index suggested that long time use of Smartphone had a strong relationship with neck pain. The first line treatment for cervicogenic headache is physiotherapy management. Objective: To check the prevalence of cervicogenic headache among young population. Methodology: Nonexperimental and observational type. Outcome Measures: Prevalence of Cervicogenic Headache Questionnaire (Self prepared questionnaire). Procedure: Subjects were selected according to inclusion criteria; the questionnaires were sent and later it was scored, and statistics were made. Results: The study shows that there is prevalence of cervicogenic headache among young population. Among the 272 individuals 26 individuals showed proneness to cervicogenic headache. Conclusion: the study concludes that there is 10.4% prevalence and proneness of cervicogenic headache among young population, it can be due to the strain in the neck while using Smartphone, laptops or while doing other activities like studying, playing games.